2017
DOI: 10.21037/jtd.2017.05.51
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of acute respiratory failure in a patient with pulmonary Mycobacterium abscessus infection accompanied by organizing pneumonia

Abstract: Organizing pneumonia (OP) is an inflammatory lung disease characterized pathologically by the presence of buds of granulation tissue in the distal air spaces. There are numerous causes of OP including acute respiratory infections such as viral and bacterial infections. However, Mycobacterium abscessus (M. abscessus) has rarely been reported as a causative pathogen of OP. Here, we report a 67-year-old woman with rapidly progressive pulmonary M. abscessus infection who developed OP and acute respiratory failure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Patients with severe pulmonary infections have limited systemic activity and reduced ability to excrete sputum independently, which can result in thick sputum and the accumulation of secretions, and thus increases the risk of airway blockage (10,11). Studies have shown that the treatment of severe pulmonary infections should focus on fighting the infection, removing foreign bodies in the respiratory tract, and ensuring that the respiratory tract is clear of blockages (12). Studies have also found that current anti-infective treatments for severe pulmonary infections are not ideal.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with severe pulmonary infections have limited systemic activity and reduced ability to excrete sputum independently, which can result in thick sputum and the accumulation of secretions, and thus increases the risk of airway blockage (10,11). Studies have shown that the treatment of severe pulmonary infections should focus on fighting the infection, removing foreign bodies in the respiratory tract, and ensuring that the respiratory tract is clear of blockages (12). Studies have also found that current anti-infective treatments for severe pulmonary infections are not ideal.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 A foreign study suggested that the treatment of severe pulmonary infection focused on resisting infection, cleaning airway foreign bodies and ensuring unblocked airway. 12 Sun found that anti-infective treatment was not ideal for patients with severe pulmonary infection. 13 In recent years, fiberoptic bronchoscopy, whose therapeutic effect is significantly higher than that of ordinary sputum aspiration, has been gradually carried out in clinical practices, and it has the advantages of non-invasion and high efficiency, and can avoid the damage to airway mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…OP is rare. The exact aetiology of this inflammatory reaction remains unclear [11]. OP does not exhibit a sex predilection and is more common in older people, with a mean age of onset of 50–60 years [12].…”
Section: Discussionmentioning
confidence: 99%